Third-generation sequencing revises the molecular karyotype for Toxoplasma gondii and identifies emerging copy number variants in sexual recombinants - Xia, Jing; Venkat, Aarthi; Bainbridge, Rachel E.; Reese, Michael L.; Le Roch, Karine G.; Ay, Ferhat; Boyle, Jon P. (Genome Research, 2021)
Toxoplasma gondii is a useful model for intracellular parasitism given its ease of culture in the laboratory and genomic resources. However, as for many other eukaryotes, the T. gondii genome contains hundreds of sequence gaps owing to repetitive and/or unclonable sequences that disrupt the assembly process. Here, we use the Oxford Nanopore Minion platform to generate near-complete de novo genome assemblies for multiple strains of T. gondii and its near relative, N. caninum. We significantly improved T. gondii genome contiguity (average N50 of ∼6.6 Mb) and added ∼2 Mb of newly assembled sequence. For all of the T. gondii strains that we sequenced (RH, ME49, CTG, II×III progeny clones CL13, S27, S21, S26, and D3X1), the largest contig ranged in size between 11.9 and 12.1 Mb in size, which is larger than any previously reported T. gondii chromosome, and found to be due to a consistent fusion of Chromosomes VIIb and VIII. These data were validated by mapping existing T. gondii ME49 Hi-C data to our assembly, providing parallel lines of evidence that the T. gondii karyotype consists of 13, rather than 14, chromosomes. By using this technology, we also resolved hundreds of tandem repeats of varying lengths, including in well-known host-targeting effector loci like rhoptry protein 5 (ROP5) and ROP38. Finally, when we compared T. gondii with N. caninum, we found that although the 13-chromosome karyotype was conserved, extensive, previously unappreciated chromosome-scale rearrangements had occurred in T. gondii and N. caninum since their most recent common ancestry.
10.1101/gr.262816.120